A first principles study of the stacking fault energies for fcc Co-based binary alloys. (1st September 2017) - Tian, Li-Yun; Lizárraga, Raquel; Larsson, Henrik; Holmström, Erik; Vitos, Levente
Abstract: The stacking fault energy is closely related to structural phase transformations and can help to understand plastic deformation mechanisms in materials. Here we perform first principles calculations of the stacking fault energy in the face centered cubic (fcc) Cobalt-based binary alloys Co1− x M x, where M = Cr, Fe, Ni, Mo, Ru, Rh, Pd and W. We investigate the concentration range between 0 and 30 at.% of the alloying element. The results are discussed in connection to the phase transition between the low-temperature hexagonal close packed (hcp) and the fcc structures observed in Co and its alloys. By analyzing the stacking fault energies, we show that alloying Co with Cr, Ru, and Rh promotes the hcp phase formation while Fe, Ni and Pd favor the fcc phase instead. The effect of Mo and W on the phase transition differs from the other elements, that is, for concentrations below 10% the intrinsic stacking fault energy is lower than that for pure fcc Co and the energy barrier is higher, whereas above 10% the situation reverses. We carry out also thermodynamic calculations using the ThermoCalc software. The trends of the ab initio stacking fault energy are found to agree well with those of the molar Gibbs energy differences and the phase transition temperature in the binary phase diagrams and give a solid support for the phase stability of these alloys. Graphical abstract: